An investigation of acoustic methods for measuring the length and grout quality of rock anchors in mines - Agnew, Gary David (My University, 2016)
A demand exists in the mining industry for an instrument capable of testing rock anchors quickly, reliably and non-destructively. This report describes laboratory tests in which the acoustic pulse interrogative techniques investigated for rock anchors up to 1,9m in length, using concrete cylinders to simulate rock. [Abbreviation abstraction. Open document to view full version]
A project report submitted to the Faculty of Engineering, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg, 1990